2021
DOI: 10.35473/ijm.v4i1.894
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Indeks Massa Tubuh dengan Tekanan darah pada Remaja di SMK NU Ungaran

Abstract: AbstrakLatar Belakang: Obesitas di Indonesia mengancam anak dan remaja, dimana obesitas sentral pada remaja umur ≥15 tahun meningkat dari 26,6% (2013) menjadi 31% (2018). Obesitas berdampak secara  fisiologis dalam meningkatnya penyakit cardiovaskler seperti hipertensi. Indeks Massa Tubuh (IMT) merupakan alat skrinning untuk pengukuran jumlah lemak pada anak dan remaja yang paling mudah, sederhana dan akurat dalam mendeteksi adanya gizi lebih pada remaja. Penelitian ini bertujuan untuk mengetahui hubungan IMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…According to Widyatmoko's findings, there is a significant correlation between score of BMI and systolic-diastolic blood pressure in high school teachers. Widyatmoko's research showed that there is a significant relationship between BMI and systolic-diastolic blood pressure in high school teachers [13].…”
Section: Resultsmentioning
confidence: 99%
“…According to Widyatmoko's findings, there is a significant correlation between score of BMI and systolic-diastolic blood pressure in high school teachers. Widyatmoko's research showed that there is a significant relationship between BMI and systolic-diastolic blood pressure in high school teachers [13].…”
Section: Resultsmentioning
confidence: 99%